Picard Boundary Value Problems for Second Order Nonlinear Functional Integro-Differential Equations - Liu, Yuji (Sarajevo Journal of Mathematics, 2024)
Sufficient conditions for the existence of solutions of the Picard boundary value problem for the second order nonlinear integro-differential equation are established. We allow $G$ to grow linearly, superlinearly or sublinearly in our obtained results, see Theorem 2.1 and Theorem 2.2. Examples are presented to illustrate the efficiency of our theorems. 2000 Mathematics Subject Classification. 34B10, 34B15